2017
DOI: 10.1007/s11069-017-2867-6
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic conditions associated with cool season post-fire debris flows in the Transverse Ranges of southern California

Abstract: The Transverse Ranges of southern California often experience fire followed by flood. This sequence sometimes causes post-fire debris flows (PFDFs) that threaten life and property situated on alluvial fans. The combination of steep topography, highly erodible rock and soil, and wildfire, coupled with intense rainfall, can initiate PFDFs even in cases of relatively small storm rainfall totals. This study identifies common atmospheric conditions during which damaging PFDFs occur in the Transverse Ranges during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 56 publications
3
84
0
Order By: Relevance
“…During this event, simulated CAPE locally exceeds 200 J/kg, which is low in absolute terms but relatively high by local standards. Indeed, Oakley et al () find that the median CAPE during historical California ARs that produced extreme precipitation leading to debris flows was only on the order of 20–40 J/kg in cyclonic warm sector preceding cold frontal passage. Moreover, Monteverdi et al () find that low CAPE environments (200–400 J/kg) were typical even during tornadic thunderstorm events in this region—whereas much higher values (2,000 J/kg or more) are more typical of severe convective events elsewhere in North America.…”
Section: Resultsmentioning
confidence: 99%
“…During this event, simulated CAPE locally exceeds 200 J/kg, which is low in absolute terms but relatively high by local standards. Indeed, Oakley et al () find that the median CAPE during historical California ARs that produced extreme precipitation leading to debris flows was only on the order of 20–40 J/kg in cyclonic warm sector preceding cold frontal passage. Moreover, Monteverdi et al () find that low CAPE environments (200–400 J/kg) were typical even during tornadic thunderstorm events in this region—whereas much higher values (2,000 J/kg or more) are more typical of severe convective events elsewhere in North America.…”
Section: Resultsmentioning
confidence: 99%
“…Other recent Santa Ana Wind driven fire events, such as those that occurred in October 2003 and 2007, directly caused more deaths and destruction. However, the flooding and post-fire debris flow triggered by a landfalling atmospheric river [40] over the Thomas Fire burn scar that occurred in Montecito and Santa Barbara claimed at least another 21 lives and destroyed more than 100 homes [41].…”
Section: Southern California Firesmentioning
confidence: 99%
“…Over the past several years, interest in atmospheric river (AR) science and applications has increased rapidly. Beyond the now well‐known impacts of heavy rain and flooding (e.g., Lamjiri et al, ; Neiman et al, ; Ralph et al, ), ARs have been shown to have applications in areas as diverse as avalanche hazard (Hatchett et al, ), dust transport (Ault et al, ), and postfire debris flows (Oakley et al, ). Furthermore, the study of ARs has become global in scope, and international in terms of participation, as evidenced by the well‐attended 2018 International Atmospheric Rivers Conference (Ramos et al, ).…”
Section: Introductionmentioning
confidence: 99%